1992
DOI: 10.1128/jb.174.22.7428-7435.1992
|View full text |Cite
|
Sign up to set email alerts
|

Microcin 25, a novel antimicrobial peptide produced by Escherichia coli

Abstract: Microcin 25, a peptide antibiotic excreted by an Escherichia coli strain isolated from human feces, was purified to homogeneity and characterized. Composition analysis and data from gel ifitration indicated that microcin 25 may contain 20 amino acid residues. It has a blocked amino-terminal end. Microcin synthesis and immunity are plasmid determined, and the antibiotic was produced in minimal medium when the cultures entered the stationary phase of growth. The peptide appears to interfere with cell divrision, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
389
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(401 citation statements)
references
References 34 publications
10
389
0
2
Order By: Relevance
“…However, no morphological changes to the septa were observed with TEM. The peptides PR-39 [29], PR-26 [29], indolicidin [31] and microcin [28] were previously found to cause filamentation which may be caused by the inhibition or alteration of membrane proteins required for septum formation [4]. Sochaki and colleagues previously found that fluorescently labeled LL-37 more readily entered E. coli cells at the septal regions of dividing cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, no morphological changes to the septa were observed with TEM. The peptides PR-39 [29], PR-26 [29], indolicidin [31] and microcin [28] were previously found to cause filamentation which may be caused by the inhibition or alteration of membrane proteins required for septum formation [4]. Sochaki and colleagues previously found that fluorescently labeled LL-37 more readily entered E. coli cells at the septal regions of dividing cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…They form three classes depending on the absence (class II) or presence of one (class III) or two (class I) disulfide bridges that further stabilize the structure [6]. They exhibit a variety of biological activities, involving enzyme inhibition, receptor antagonism, antimicrobial or anti-HIV activities (see Table 1 for class II lasso peptides) [5,[7][8][9][10][11][12]. Their compact structure confers to lasso peptides a great resistance to denaturing conditions and certain proteases.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore they are considered to play a major role in the regulation of microbial competition within the intestinal flora. MccJ25 (microcin J25) is naturally secreted by the faecal Escherichia coli AY25 strain [1]. The 21-residue mature MccJ25 (2.1 kDa) was isolated from culture supernatants [2].…”
Section: Introductionmentioning
confidence: 99%